Single-cell multi-omics sequencing reveals the immunological disturbance underlying Kawasaki disease - Fan, Xue; Deng, Shuang; Xu, Yuehao; Wang, Bin; Guo, Xin; Liao, Jinwen; Xu, Mingguo (Frontiers in Molecular Biosciences, 2026)
IntroductionKawasaki disease (KD) is an acute autoimmune vasculitis that predominantly affects children under 5 years of age. Although immune dysregulation is considered central to KD pathogenesis, the cellular heterogeneity and regulatory mechanisms underlying this process remain incompletely understood. Single-cell multi-omics technologies provide an opportunity to characterize immune alterations at high resolution.MethodsPeripheral blood mononuclear cells (PBMCs) were obtained from two children with typical KD and two age-matched healthy controls. Integrated single-cell RNA sequencing (scRNA-seq) and single-cell assay for transposase-accessible chromatin sequencing (scATAC-seq) were performed to characterize immune cell composition, transcriptional profiles, and chromatin accessibility. Comparative analyses were conducted to identify altered immune cell subsets and dysregulated signaling pathways in KD.ResultsChildren with KD exhibited marked immune dysregulation, characterized by altered proportions and functional states of multiple PBMC subsets, including T cells, B cells, and natural killer (NK) cells. Notably, specific NK cell subsets were associated with the pathogenesis of intravenous immunoglobulin (IVIG)-resistant KD. Pathway analyses revealed significant dysregulation of toll-like receptor signaling, B cell and T cell receptor signaling, Th17 and Th1/Th2 differentiation, NK cell–mediated cytotoxicity, and platelet activation pathways.DiscussionBy integrating scRNA-seq and scATAC-seq data, this study delineates the heterogeneity of immune cell populations in KD at the single-cell level. The findings highlight coordinated immune and platelet activation pathways that may contribute to KD-associated inflammation and IVIG resistance. These results provide mechanistic insights into KD immunopathogenesis and suggest potential cellular and molecular targets for therapeutic intervention.